Computer Anxiety and Computer Attitude towards Computer Self Efficacy (CSE) Polsri Telecommunication Engineering Student on Writing the Final Report - Irma Salamah; M. Aris Ganiardi; RD Kusumanto (IAES Indonesia Section, 2015)
Various attitudes emerged and shown byindividuals for the presence of computer. Although manybenefits are felt by the computer, but there are some peoplewho feel anxious with the computer (computer anxiety).Computer attitude showed no reaction or behave the computerby pleasure or displeasure against the computer. Thephenomenon that arises is computer anxiety and computerattitude can affect a person's expertise in the use or operate thecomputer. This study aims to examine how the effect ofcomputer anxiety and computer attitude towards computer selfefficacy on the 6th semester student telecommunicationsengineering POLSRI. Samples taken in this study were allstudents of telecommunication engineering 6th semesterPOLSRI totaling 89 people. The results showed computeranxiety and computer attitude not affect the computer selfefficacy6th semester student of telecommunicationsengineering POLSRI. This is due because the 6th semesterstudent of telecommunications engineering POLSRI havepositive feelings to learn the computer either by themselves orthrough a learning courses.They also realize that the computerprovides many benefits. With the computer, the informationcan be obtained more quickly and efficiently. Computer is anecessity, can enhance human life, and was instrumental ineducation and employment.